The Role of Mind Mapping Media in Revealing Primary School Students' Critical Thinking Abilities - Astuti, Diana Dini; Mustoip, Sofyan; Aljulia, Nita (LJPI UI Bunga Bangsa Cirebon, 2024)
This research aims to explore the role of mind mapping media in developing students' critical thinking skills in elementary schools. Mind mapping media is known as a visual aid that can help students organize information and connect ideas in a more structured way. This research uses a qualitative approach with a case study method in an elementary school. Data was collected through in-depth interviews with teachers, classroom observations, and analysis of learning documents involving the use of mind mapping media. The research results show that the use of mind mapping media can stimulate students' critical thinking abilities by improving their analysis, synthesis and information evaluation skills. In addition, students also showed improvements in their ability to solve problems and collaborate in groups. These findings provide new insight into how mind mapping media can be integrated into the learning process to improve the quality of students' thinking at the elementary school level.